City as a Theater Space in the Paintings of OST Artists - Bulatova, Maria A. (Actual Problems of Theory and History of Art, 2013)
In this article we are exploring the city image in the paintings of OST artists considered in the light of the theater perception and specifics of the stage space. We have selected a number of as-pects permitting to talk about the stage adaptation of life and human habitat. By analysing some famous paintings of OST artists, the dependence of painting on the “theatrical” way of thinking of the painters can be proved.
Keywords: art of the 20th century; OST; theater; theater space; the city image